Water quality assessment and trends in twin cities of Pakistan: a review - Kashaf Waseem; Abdul Saboor Akhtar; Ahsan Nawaz; Muhammad Saeed (Discover Water)
Abstract Water quality is a significant determinant of ecosystem health and human well-being particularly in cities undergoing rapid industrialization and population growth. This review highlights data from studies conducted between 2004 and 2024 to assess the water quality of surface and groundwater sources in Islamabad and Rawalpindi. The results indicate severe microbial contamination with high levels of total coliform, fecal coliform, and E. coli in both cities, with a potential risk of waterborne diseases. Heavy metal contamination exists, especially As and Pb, which is significantly higher in Rawalpindi due to the industries. Physicochemical parameters, such as turbidity and residual microbial contamination remain in treated water, implying inefficiency in the water treatment process. The contamination also shows seasonal fluctuation, increasing during monsoon due to sewage overflows and agricultural runoff. Both cities also have conventional water treatment infrastructure that causes widespread contamination in the distribution system. Public health impact is prevalent, and outbreaks of diseases from waterborne diseases including Hepatitis E reported both in urban and peri-urban areas quite frequently. A gap is critical in applying the Advanced Oxidation Process (AOP) and other emerging technologies for degrading persistent contaminants, most notably heavy metals and microbial pollutants in the AOPs. This review focuses on the urgency of upgrading infrastructure, strengthening the implementation of water quality standards, and using more advanced treatment technologies and offers recommendations to policymakers and stakeholders and technology solutions for tackling critical challenges in water quality management, and emphasizes the importance of continuous monitoring and the enforcement of regulations. Graphical Abstract